No More ‘Yes Girls’:: Labour Activism among New Brunswick Nurses, 1964-1981 - Kealey, Linda (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2008)
Abstract Beginning in the 1960s, New Brunswick nurses awoke to the fact that little value was placed on their work. By the mid-1960s they began to explore collective action within their professional association, the New Brunswick Association of Registered Nurses. With the passage of a new labour relations act in the late-1960s nurses gained collective bargaining rights, including the right to strike. This article examines three key moments of labour conflict – 1969, 1975, and 1980-81 – that help to explain the nurses’ turn towards unionization.